Trends in Ultra-Processed Food Consumption and Its Correlation to Obesity Risk in Urban Adolescents - Zuhrotunida Zuhrotunida; Irwan Hadi; Annisa Andriyani (PT. Anagata Sembagi Education, 2025)
The trend of ultra-processed food (UPF) consumption among urban adolescents has increased along with the modern, fast-paced lifestyle. This consumption pattern has the potential to increase the risk of obesity, especially in school-age groups. This study aims to analyze the relationship between the level of ultra-processed food consumption and the risk of obesity in adolescents based on Body Mass Index (BMI). The study was conducted with a quantitative approach and cross-sectional design on 200 high school students in the DKI Jakarta area. Data were collected through a Food Frequency Questionnaire (FFQ) and anthropometric measurements (weight and height). The analysis technique used the Kolmogorov-Smirnov normality test, Pearson correlation test, and simple linear regression with a significance level of p < 0.05. The results showed that the majority of respondents consumed ultra-processed foods in the moderate to high category. The highest average BMI was recorded in the high UPF consumption group (24.3), while the low consumption group had an average BMI of 21.4. The Pearson correlation test yielded an r value of 0.479 (p = 0.000), and linear regression showed a 23% contribution of UPF consumption to BMI variation (R² = 0.230). This study concluded that there is a significant positive relationship between ultra-processed food consumption and obesity risk in urban adolescents. These results provide an important basis for strengthening nutrition education programs, limiting unhealthy food advertising, and implementing healthy canteen policies in school environments.